Analisis Ilmu Bayan pada Syi’ir al-Bahtsu ‘an as-Sa’adah Karya Nazik al-Malaikah - Sayyid An-Nabiil, Muhammad; Sarifudin, Mukhamad (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2024)
This research will include an analysis of majaz in Nazik Al-Malaikah's poem entitled Al-Bahtsu 'an As-Sa'adah. This poem contains a theme about the search for happiness in life that can be obtained through various paths or ways. The words in this poem are beautiful, but seem symbolic so that they seem to mean something else that cannot be understood. The purpose of this research is to explain the poem Al-Bahtsu 'an As-Sa'adah by using bayan science. The method used in this research is descriptive qualitative. This research is included in library research which uses the poem entitled Al-Bahtsu 'an As-Sa'adah by Nazik Al-Malaikah as the primary source. The secondary sources in this research use several books, journals and works that are relevant to this research. The result of this research is that the poem Al-Bahtsu 'an As-Sa'adah has majaz isti'arah which is used by the poet as a means of expressing the meaning of the search for happiness. Lafaz used as majaz isti'arah are lafaz that have a similarity relationship or 'alaqah musyabihah between the real and majazi meanings. In addition, this poem also contains another type of majaz, namely majaz mursal.